2012
DOI: 10.1186/1471-2334-12-193
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacterantimicrobial resistance in Peru: a ten-year observational study

Abstract: BackgroundCampylobacter jejuni and Campylobacter coli are food-borne pathogens of great importance and feature prominently in the etiology of developing world enteritis and travellers’ diarrhoea. Increasing antimicrobial resistant Campylobacter prevalence has been described globally, yet data from Peru is limited. Our objective was to describe the prevalence trends of fluoroquinolone and macrolide-resistant C. jejuni and C. coli stool isolates from three regions in Peru over a ten-year period.MethodsSurveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 41 publications
(90 reference statements)
4
64
1
3
Order By: Relevance
“…As a zoonotic pathogen transmitted through the food-borne route, Campylobacter is subject to selection pressure from macrolide use in both veterinary medicine and human medicine. Although the overall prevalence of macrolideresistant Campylobacter is relatively low, high incidences of macrolide resistance in Campylobacter have been reported in some studies (5)(6)(7)(8)(9). In order to curb the emergence of macrolide resistance, it is necessary for us to understand how Campylobacter develops resistance to this class of antibiotics.…”
mentioning
confidence: 99%
“…As a zoonotic pathogen transmitted through the food-borne route, Campylobacter is subject to selection pressure from macrolide use in both veterinary medicine and human medicine. Although the overall prevalence of macrolideresistant Campylobacter is relatively low, high incidences of macrolide resistance in Campylobacter have been reported in some studies (5)(6)(7)(8)(9). In order to curb the emergence of macrolide resistance, it is necessary for us to understand how Campylobacter develops resistance to this class of antibiotics.…”
mentioning
confidence: 99%
“…This increase emerged after the licensure of fluoroquinolones (sarafloxacin and enrofloxacin) for use in poultry and in general veterinary medicine (Ruiz-Palacios 2007). Several investigations have demonstrated that an increased prevalence of fluoroquinolone resistance among animals and human Campylobacter isolates is temporally related to the use of fluoroquinolones in veterinary medicine (Smith and Fratamico 2010, Engberg et al 2001, Moore et al 2006, Ruiz-Palacios 2007, Pollett et al 2012, Nelson et al 2007, Endtz et al 1991.…”
Section: Campylobacter and Fluoroquinolone Resistancementioning
confidence: 99%
“…An alarming increase in Campylobacter fluoroquinolone resistance has been documented in many countries (Pollett et al 2012). This increase emerged after the licensure of fluoroquinolones (sarafloxacin and enrofloxacin) for use in poultry and in general veterinary medicine (Ruiz-Palacios 2007).…”
Section: Campylobacter and Fluoroquinolone Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…O período de incubação é normalmente de 2 a 5 dias, podendo se estender por até 2 semanas (Butzler, 2004;Young et al, 2007). Em casos mais graves, onde a reposição hidroeletrolítica não se faz suficiente, o uso de antimicrobianos é recomendado (Snelling et al, 2005;Pollett et al, 2012).…”
Section: Manifestações Clínicas E Patogêneseunclassified